Critical Thinking through Three Levels of Representation: An Analysis of Carbohydrate Concepts in Chemistry Textbooks - Nurhalimah Hasibuan; Sjaeful Anwar; Heli Siti Halimatul Munawaroh (International Journal of STEM Education for Sustainability, 2026)
For a student to gain a deeper understanding of concepts in chemistry, they need to learn concepts at three levels of representation: macroscopic, submicroscopic, and symbolic. The three levels of representation of information are crucial for developing critical thinking skills. But the textbook, which is the main learning resource, plays a vital role in helping a student relate concepts at the three levels. The objective of this research was to assess the display of carbohydrate representation at three levels in ten general chemistry textbooks. In order to examine 120 visual representations, this research employed qualitative content analysis, with five criteria developed from the work of Gkitzia et al. (2020). Criteria C1-C5 include the following: type of representation (C1), interpretation of surface characteristics (C2), relationship to text (C4), presence and nature of captions (C5), and level of correlation between elements that comprise the different representations. Thirdly, the usefulness of the proposed criteria was compared to chemistry textbooks. The results showed that there was a dominance of representations at the symbolic level. Moreover, some of the representations were found to have insufficient subtitles to give meaning, especially at the submicroscopic level. The conceptual understanding of students can be impaired by the dominance of symbolic representations and the absence of visual support for other levels. To ensure that critical thinking is done effectively, this study stresses the need to develop learning materials that incorporate the three levels of representation in a balanced manner. These five criteria can also be used to analyze existing school textbooks and to design new Chemistry textbooks.